ANALISIS PERKEMBANGAN PRODUKSI SARUNG TENUN GOYOR PADA MASA PANDEMI - Tania Putri Novita Sari; Anggita Nanda Oktaviani; Roihatul Janah (MANAJEMEN, 2022)
The fact of industrial development is that in Wanarejan village, Pemalang city is famous for the production of woven fabrics and is a characteristic of the village. so the purpose of this study is to describe the analysis of developments contained in the home industry of weaving in the village of Wanarejan. In this study, the population used were entrepreneurs of goyor woven fabrics. This research is a research with a qualitative approach with descriptive data type, which is trying to present objective facts in accordance with the conditions that occurred at the time the research was conducted. Data collection techniques in this study using observation, interviews and documentation. The results of this study found that the production of woven sarongs is still in demand by people in Pemalang City and in other cities. Sales of this woven sarong export to various countries. Woven fabric products have their own characteristics because of the use of simple weaving techniques with non-machine looms, thus adding a more beautiful, smooth and neat impression. The hallmark of the goyor woven sarong that makes it a fashion with its traditional characteristics lies in its design and good quality level.